Fintech competencies in emerging markets: Cognitive hybrid decision-making approach - Rahadian, Dadan; Firli, Anisah; Yüksel, Serhat; Dinçer, Hasan (My University, 2024)
The purpose of this study is to make a priority analysis for the factors affecting fintech competency for emerging markets. A novel 3-stage decision-making model has been established to reach this objective. First, missing evaluations are completed by using recommender systems. The next stage includes the weight calculation of the criteria via quantum spherical fuzzy cognitive maps. The final stage gives information about the ranking of BRIC countries (Brazil, Russia, India, China) for the fintech competency performance. It is defined that technological infrastructure plays the most crucial role in this regard.
Keywords: Emerging Markets; Fintech Competencies; Investment Decision; Strategic Management